Temperature and Rainfall on Growth and Development of ‘Kimju’ Guava (Psidium guajava) - Jirapaet, Jakkrapong; Jaidee, Thanakrit; Poonthep, Sudarat (Princess of Naradhiwas University Journal, 2021)
This research aimed to study the changes of temperature and rainfall on growth and development of ‘Kimju’ guava and to study the growth patterns and phenology for each developmental phase of ‘Kimju’ guava. The experimental site was at Faculty of Agriculture, Princess of Naradhiwas University. The weather information including rainfall, maximum and minimum temperature from January to June 2019 was recorded. The collection data were the growth, the changes in each growth and development phase by BBCH scale, which consisted of new shoot length, flower size and fruit size. The collection data were randomly in 5 samples per plant from 30 trees. The fullness of plant growth was studied by calculating the cumulative heat unit of temperature. The relationship between climate data and the growth, the growth patterns and phenology of ‘Kimju’ guava with the period of time were studied by linear regression analysis. The results found that from January to June 2019 the total rainfall, maximum, and minimum temperatures were 646.7 mm, 32.6 and 24.3oC, respectively at Mueang District, Narathiwat Province. These data was related and suitable for the growth of ‘Kimju’ guava. The accumulate heat unit until harvest stage was 2,222.5-2,380.4 CDD. The growth patterns and phenology of ‘Kimju’ guava which include bud development, leaf development, inflorescence emergence, flowering, fruit development and fruit ripening gave relationship with time. The growth of new shoots and flowers showed a pattern of sigmoid curve and fruit development showed a double sigmoid curve.